2004
DOI: 10.4161/cc.3.11.1212
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile at the G1/S Transition of Liver Regeneration after Partial Hepatectomy in Mice

Abstract: Liver is a quiescent organ with >90% of the cells present in the G 0 stage of the cell cycle. However, adult hepatocytes have enormous ability to proliferate in response to liver injury. After 70% liver resection hepatocytes enter the cell cycle in a highly synchronized manner and undergo 1 to 2 rounds of cell division to restore the lost organ mass, thus, representing one of the most reliable model systems to study cell cycle progression in vivo. Using high density oligonucleotide micro-array we analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
2
3
0
Order By: Relevance
“…We have previously shown that in our ex vivo culture system, primary mouse hepatocytes complete DNA replication after 48 h of HGF stimulation (Huard et al , 2012 ). This result is congruent with in vivo data of partially hepatectomized mice where the peak of DNA synthesis occurs between 36 and 48 h post-surgery (Satyanarayana et al , 2004 ; Michalopoulos, 2007 ). Furthermore, we determined that the restriction point occurs after approximately 32 h of HGF stimulation in primary mouse hepatocytes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have previously shown that in our ex vivo culture system, primary mouse hepatocytes complete DNA replication after 48 h of HGF stimulation (Huard et al , 2012 ). This result is congruent with in vivo data of partially hepatectomized mice where the peak of DNA synthesis occurs between 36 and 48 h post-surgery (Satyanarayana et al , 2004 ; Michalopoulos, 2007 ). Furthermore, we determined that the restriction point occurs after approximately 32 h of HGF stimulation in primary mouse hepatocytes.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we determined that the restriction point occurs after approximately 32 h of HGF stimulation in primary mouse hepatocytes. This is in line with gene expression studies addressing the G1/S transition after two-thirds PHx in C57BL/6 mice that identified a time frame of 30–36 h for this crossing point (Satyanarayana et al , 2004 ). These data indicate a good correlation for the timing of the G1/S transition and the restriction point between mouse hepatocytes ex vivo and in vivo .…”
Section: Discussionsupporting
confidence: 82%
“…Liver regeneration entails the activation of multiple regulatory pathways that include cytokine-, growth factor-, and metabolic networks [40]. More specifically, PHx induces differential regulation of genes that coordinate cell cycle regulation, chromatin reorganization, transcriptional regulation, signal transduction, protein targeting, metabolism, transport, xenobiotic metabolism, surface receptors, inflammation, and acute phase responses [41]. These pathways are well- coordinated to allow proper restoration of the tissue while maintaining vital liver functions.…”
Section: General Mechanisms Of Liver Regeneration Following Partial Hmentioning
confidence: 99%
“…For example, Saa3 transcript expression was increased following NSC administration. Saa3 is an acute phase reactant specific to mice, a pseudogene in humans, that has been shown to be associated with liver regeneration following partial hepatectomy and may be important for metabolic adaptation and cellular protection ( 56 , 57 ). Notable genes that were downregulated by NSC treatment included Egr2 and Ddit3 .…”
Section: Discussionmentioning
confidence: 99%